(untitled) (Czech Journal of Multidisciplinary Innovations, 2022)
This research aims to assess the level of satisfaction of master’s and doctoral students. Faculty of Economics and Business Administration on performance of websites that market books, references and educational tools; Including computers, and other educational products needed by postgraduate students in the master’s and doctoral stages, Business Administration department. The study focused on assessing the level of students’ satisfaction according to a number of criteria; the most important ones are: quality, timing, price and quantity. It is cleared that students’ attitudes showed high positive scores; meaning high levels of satisfaction of dealing with these sites according to the scores of the arithmetic mean and standard deviations shown by the statistical analysis. These findings should enhance e-applications for other products and services marketers in all sectors for achieving needed accuracy, quality and low expenses, and highest customers’ satisfaction